2023
DOI: 10.1039/d2bm01894b
|View full text |Cite
|
Sign up to set email alerts
|

Injectable hydrogel loaded with 4-octyl itaconate enhances cartilage regeneration by regulating macrophage polarization

Abstract: In this study, the OSA/GEL hydrogel was successfully fabricated as a vehicle for delivering 4-OI, which could evidently alleviate the inflammatory reaction and thus accelerate tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…4-OI alleviates tissue injury and regulates immune balance via activation of the Nrf2 signaling pathway [ 42 , 43 ]. For example, Xiao et al loaded 4-OI into an oxidized sodium alginate/gelatin hydrogel to treat cartilage damage and confirmed that the developed hydrogel was able to promote M2 macrophage polarization and inhibit inflammatory responses, thus promoting cartilage regeneration [ 44 ]. However, little has been reported about the application of 4-OI for the treatment of fractures and bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…4-OI alleviates tissue injury and regulates immune balance via activation of the Nrf2 signaling pathway [ 42 , 43 ]. For example, Xiao et al loaded 4-OI into an oxidized sodium alginate/gelatin hydrogel to treat cartilage damage and confirmed that the developed hydrogel was able to promote M2 macrophage polarization and inhibit inflammatory responses, thus promoting cartilage regeneration [ 44 ]. However, little has been reported about the application of 4-OI for the treatment of fractures and bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies are beginning to elucidate ITA's role in promoting M2 macrophage polarization as well [ 45 ]. For example, a hydrogel loaded with ITA derivative, 4-octyl itaconate (OI), resulted in M2 macrophage polarization [ 46 ], and DMI-loaded PCL nanofibers polarized M1 macrophages into M2 macrophages [ 47 ]. Notably, our results show that the PICO patch was the only material that demonstrated an increase in the CD206 expression over time, which could correspond to M2 macrophage polarization upon release of ITA from the patches, which occurs to a much greater extent at 6 weeks compared to 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…78 And alginate can also be modified to cross-link with other materials. Sodium oxidized alginate (OSA) and gelatin (GEL) loaded with 4-octanoic acid (4-OI), a derivative of the endogenous metabolite itaconic acid, promote the polarization of M2 macrophages and inhibit the inflammatory response, and promote cartilage regeneration at a later stage 79 (Figure 4B).…”
Section: Alginate For Cartilage Repairmentioning
confidence: 99%
“…(B) Sodium oxidized alginate (OSA) and gelatin (GEL) loaded with 4-octanoic acid (4-OI), a derivative of the endogenous metabolite itaconic acid, promote the polarization of M2 macrophages, inhibit the inflammatory response, and promote cartilage regeneration at a later stage. Reproduced with permission from ref . Copyright 2023 Royal Society of Chemistry.…”
Section: Overview Of Polysaccharide-based Polymers and Their Propertiesmentioning
confidence: 99%